Analysis of the Utilization of Digital Technology in the Flipped Learning Model to Improve Students’ Conceptual Understanding - Sulkipli M; Hidayani Hidayani; Andi Maryam; Ainun Mardiah; Grace Christie Aulia (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the effectiveness of the utilization of digital technology in the flipped learning model on improving students’ conceptual understanding. This study used a quasi-experimental design with a nonequivalent control group approach involving two classes of students: the experimental class (32 students) and the control class (33 students). The research instruments consisted of pretests and posttests and observation sheets, which were then analyzed using descriptive statistics, t-tests, and N-Gain. The results of the study showed a significant difference in the mean between the experimental and control groups, with t = –9.206 and Sig. (2-tailed) <0.001, indicating that the implementation of digital technology in flipped learning significantly influences students’ conceptual understanding. The N-Gain value indicated that the improvement in the experimental class was in the moderate to high category, while the control class was predominantly in the low category. Thus, it can be concluded that the flipped learning model based on digital technology is more effective and positively affects students’ conceptual understanding, particularly by increasing active engagement and independence in learning, compared to the traditional learning approach